Improving activity data for Tier 2 estimates of livestock emissions: Dealing with data gaps - Wollenberg, Eva Karoline; Leahy, Sinead; Clark, Harry (2018)
Expert workshop on Improving activity data for Tier 2 estimates of livestock emissions: Dealing with data gaps July 17-18, 2018 End of workshop summary Lini Wollenberg, Sinead Leahy, Harry Clark